Funding the Nigerian university education: the role of the various stakeholders (2007)
This paper addresses the issue of funding the education in Nigeria. The study sampled various stakeholders in the sector including parents, university management and administrators, students, academic staff, tax-payers, company executives to determine the level of funds available to the university system in Nigeria, to produce quality graduates and what could be done to ameliorate the shortfall. Percentages and chi-square statistics were used to analyse the data. Among the findings were the current level of insufficient, the burden of funding is almost solely on government and parents, most whom live below poverty line, the corporate bodies are seemingly averse to funding education and would rather prefer to sponsor sports and other shows such as gambling that easily attract publicity.Also the present rot in the sector is larrgely due to lack of sufficient fund to finance education. Recommendations were made based on these findings: corporate world in Nigeria, apart their contribution to the Education Task Fund, should invest in university education in order to address the current abysmal decadence in the system. Well-to-do individuals should endow these institution and fund researchers as well.